Ventiseiesimo Rapporto sulle migrazioni 2020 - Fondazione ISMU, [organisation] (FrancoAngeli, 2021)
The 26th Report on migrations by ISMU Foundation situates migration phenomena in Italy within the broader framework of the sudden outbreak and spread of COVID-19. The report analyzes the enduring impact of the pandemic on migration flows as well as on foreign residents in Italy. Statistical aspects and analyses of health, labour, and education are complemented with an in-depth study of the Italian legal framework, with particular regard to the most important legislative innovation on migration introduced in 2020: the regularization of migrant workers. The report is further complemented with detailed analyses of the link between immigration, politics, and the media, of racism, and of discrimination during the pandemic. Finally, the report devotes particular attention to the European arena, focusing on the new perspectives for European migration policy.